2019
DOI: 10.1101/2019.12.31.891671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of germ-free mosquitoes via transient colonisation allows stage-specific investigation of host-microbiota interactions

Abstract: 15The mosquito microbiota impacts the physiology of its host and is essential for normal larval 16 development, thereby influencing transmission of vector-borne pathogens. Germ-free 17 mosquitoes generated with current methods show larval stunting and developmental deficits. 18Therefore, functional studies of the mosquito microbiota have so far mostly been limited to 19 antibiotic treatments of emerging adults. In this study, we developed a novel approach to 20 produce germ-free Aedes aegypti mosquitoes. It is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…In addition to the expected differences between life stages, we found that most of the transcriptional changes were related to metabolic processes. This is consistent with other studies suggesting that bacteria play a nutritional role during larval development in mosquitoes [28,32] and fruit flies [33,34]. This is also in line with the results from a transcriptional comparison of axenic and gnotobiotic Ae.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to the expected differences between life stages, we found that most of the transcriptional changes were related to metabolic processes. This is consistent with other studies suggesting that bacteria play a nutritional role during larval development in mosquitoes [28,32] and fruit flies [33,34]. This is also in line with the results from a transcriptional comparison of axenic and gnotobiotic Ae.…”
Section: Discussionsupporting
confidence: 93%
“…It has been proposed that bacteria in the larval gut provide the essential micronutrient riboflavin (vitamin B2), whose lack results in gut hypoxia and developmental arrest [29][30][31]. Other studies suggested that the role of bacteria during larval development is primarily nutritional [28], possibly by contributing to folate biosynthesis and/or by enhancing energy storage [32]. This is consistent with work in Drosophila showing that larval gut bacteria cooperate to establish an integrated nutritional network supporting host growth [33,34].…”
Section: Introductionsupporting
confidence: 71%
“…Functional studies stemming from experimental models of ticks with manipulated inner bacterial ecosystems only start to appear, keeping pace with other symbiotic systems (see below). In mosquito research, two main protocols have been developed describing the development of axenic mosquitoes: (i) the use of disinfectants on oviposited eggs (Coon et al, 2014;Correa et al, 2018) and (ii) using a transient colonization/decolonization approach (Romoli et al, 2021). It has been demonstrated that axenic mosquitoes do not show any developmental retardation, reach the same size as controls (Correa et al, 2018;Romoli et al, 2021), and can therefore be reared under axenic conditions for multiple generations, similarly to mice and fruit flies (Steven et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental axenic or dysbiosed variants of blood-feeding arthropod species have been instrumental in understanding the functional integration of microbes into the physiology of their hosts (Narasimhan et al, 2014;Romoli et al, 2021;Gilliland et al, 2022). While mosquitoes are inhabited by a substantial amount of bacterial biomass, its functional significance in mosquito physiology and development appears to be minor, if any, under the conditions examined (Steven et al, 2021).…”
Section: Introductionmentioning
confidence: 99%